Transformation of Pancoran Village through Education Tourism and Green Environment Management for Sustainable Empowerment - Gumilang, Dendi Anggi (Sekolah Tinggi Manajemen IPMI, 2025)
Community service in Pancoran RW 04 Village, South Jakarta, is carried out with an approach based on